Psychological adaptation and peculiarities of melatonin synthesis in women with infertility of various genesis - A. V. Kaminskyi; T. V. Kolomiichenko (Zaporožskij Medicinskij Žurnal)
To improve medical care for families suffering from infertility, a comprehensive approach is needed taking into account the psychoemotional state of a woman and the adaptive capabilities of her body.